Kasus Prostitusi Perspektif Fikih Jinayah - Wahyu Fitrianoor (STAI AL FALAH Banjarbaru, 2022)
Commercial sex workers have become a ghost in our society, just like pornography, which every time there is a government action to be disbanded, or eradicated, but will always exist and continue to exist, so what's the problem? The history of mankind is also not far from this, and it can be understood that this is caused by bad habits that are approved by most people, and there is no accurate action to take preventive action or even decisive action. The Jurisprudence of jinayah in responding to this case focuses on eradicating the disease of society itself, especially this adultery. To be able to fight it, it must involve 3 important elements, 1) those who have the power to enforce the law and provide strict sanctions, 2) those who actively educate through lectures, da'wah, or create good content, and 3) the basic layer of society, namely families who guide and direct their children to get to know the laws, teachings, and procedures for socializing in accordance with Islamic teachings.Keywords: Jinayah Jurisprudence, Prostitution, Islamic Law